2019
DOI: 10.3390/ani9100755
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding Cold-Pressed Sunflower Cake on Ruminal Fermentation, Lipid Metabolism and Bacterial Community in Dairy Cows

Abstract: Simple SummaryThe use of cold-pressed sunflower cake, a by-product of small-scale biodiesel manufacturing, as a substitute for prilled palm fat in dairy cows’ diet, can reduce the extent of unsaturated fatty acid biohydrogenation This favors an accumulation of vaccenic acid in the rumen concomitant with a greater daily duodenal microbial N flow and all without impairing ruminal fermentation, microbial diversity or abundance of dominant populations. In the present study, only changes in relative abundances of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
4
5
0
Order By: Relevance
“…The C18:1 trans-11 (VA) increased in response to CPSC feeding. This response agrees with the increased VA concentration observed in rumen of the same cows fed CPSC [25] and is in line with the findings of Benhissi et al [7] who reported that, due to its elevated linoleic acid content, CPSC may inhibit the last step of biohydrogenation, increasing the ruminal outflow of VA and enhancing the deposition of this healthy FA in ruminant-derived products. Surprisingly, CPSC-induced variation in milk fat VA was not accompanied by relevant differences in C18:1 trans-10, a FA with an uncertain involvement in human coronary heart disease [29].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The C18:1 trans-11 (VA) increased in response to CPSC feeding. This response agrees with the increased VA concentration observed in rumen of the same cows fed CPSC [25] and is in line with the findings of Benhissi et al [7] who reported that, due to its elevated linoleic acid content, CPSC may inhibit the last step of biohydrogenation, increasing the ruminal outflow of VA and enhancing the deposition of this healthy FA in ruminant-derived products. Surprisingly, CPSC-induced variation in milk fat VA was not accompanied by relevant differences in C18:1 trans-10, a FA with an uncertain involvement in human coronary heart disease [29].…”
Section: Discussionsupporting
confidence: 91%
“…The lower content of C12:0 and C16:0 in milk can be primarily accounted for their lower contents in CPSC diet, but also for the increased supply of long-chain FA, mainly linoleic acid, that might have a potential inhibitory effect on de novo synthesis of short and medium chain SFA in the mammary gland of CPSC-fed cows [24]. The higher content of C18:0 can be attributed to the increased supply of linoleic acid for C18:0 synthesis in the rumen, and the greater ruminal escape of C18:0 in the same CPSC-fed dairy cows [25].…”
Section: Discussionmentioning
confidence: 99%
“…The higher proportion of ruminal C18:0 found with CPRC can be due to the fact that the CPRC diet provided greater amounts of C18 UFAs compared with the CTR diet. Other authors have observed the same trends using CPRC [9] and cold-pressed sunflower cake, also rich in C18 UFAs [36].…”
Section: Discussionsupporting
confidence: 68%
“…The amount of 16S rRNA sequencing data is affected by the sequencing technology and the sample size. Previous studies in Holstein, Jersey cow, Brown Swiss dairy cows have shown that the accurate and reliable results can be obtained if the sequencing depth is greater than 10 000 reads for each sample (Myer et al 2015;Paz et al 2016;Zubiria et al 2019). In this study, the number of reads in individual samples of rumen and jejunum greater than 40 000, and the flattened rarefaction curves indicated that we obtained sufficient sequencing amounts.…”
Section: Microbial Diversity In the Rumen And Jejunum Of Xinong Saanen Dairy Goatssupporting
confidence: 55%